Repurposing of the small-molecule adrenoreceptor-inhibitor carvedilol for treatment of the fibrotic lung - Jordan, Maria; Schmidt, Kevin; Fuchs, Maximilian; Just, Annette; Pfanne, Angelika; Willmer, Lena; Neubert, Lavinia; Werlein, Christopher; Zardo, Patrick; Pich, Andreas; Thum, Thomas; Fiedler, Jan (Frontiers in Pharmacology, 2025)
IntroductionIdiopathic pulmonary fibrosis (IPF) is a chronic fibrotic lung disease with high mortality. Current therapies are very limited, with nintedanib and pirfenidone being the only non-invasive but non-curative interventions, ultimately bridging to lung transplantation.MethodsIn silico modeling of dysregulated pathways in IPF and screening for putative interfering small molecules identified carvedilol as a promising anti-fibrotic agent. We validated drug-mediated effects on key features of fibroblast activation in functional assays and gene expression analyses in human embryonic lung fibroblasts (MRC-5). Precision-cut lung slices (PCLSs) generated from human lung tissue were assessed for secreted fibrotic markers’ expression.ResultsTreatment with carvedilol reduced metabolic activity, inhibited cell proliferation, and led to decreased migratory activity, as observed in scratch wound assays, in human lung fibroblasts. The functional profile was reflected at the transcriptional level as commonly known fibrotic marker genes, e.g., alpha smooth muscle actin and collagen 1, were robustly repressed. Proteomic profiling underlined a strong extracellular matrix interference with elevated syntheses of several collagen types and various integrins, which play a critical role in pro-fibrotic downstream signaling. Comparison of healthy and fibrotic lung tissue validated an upregulation of pro-fibrotic miR-21 secretion in the ex vivo PCLS model, which remained unchanged upon carvedilol therapy.ConclusionHerein, carvedilol demonstrated significant anti-fibrotic effects on human lung fibroblasts in vitro, thus presenting great potential as an anti-IPF treatment. In addition, miR-21 was validated as a secreted pro-fibrotic biomarker in the ex vivo PCLS model.